Towards planned cities : case study : Petaling Jaya Old Town - 455760 Lau, Wai Seang
The desire to create totally new communities organised on assumptions different from those of the larger society has inspired individuals over a long time. 'Planted' towns, or towns purposefully designed and built by a controlling agent, as opposed to 'organic' towns which have developed and grown without benefit of centralised planning, are attractive precisely because they provide the creator with the opportunity to restructure society in accordance with his principles. 'Planned Cities' or 'New Towns' are contemporary examples of these planted towns. In Malaysia, numerous planned cities had been created too. It is the aim of this dissesrtation to study the experience of only one of these planned cities, viz Petaling Jaya, as it was the first model of a planned city in Malaysia. To begin with, the historical perspective of Petaling Jaya is studied to understand the goal of creating Petaling Jaya. Subsequently, the problems of Petaling Jaya Old Town (the origin of Petaling Jaya) are analysed from various aspects, viz landuse, economic, population and housing, transportation, and public services. Lastly, the authoress forwards her suggestions an comments for reinforcing the role of Petaling Jaya old Town. The lessons learnt from the past experience of Petaling Jaya can be usefully employed as guidelines in the future developments of planned cities in our country.